Interactions at the point of firearm purchase and subsequent use of locking devices - Shelby L. Bandel; Allison E. Bond; Michael D. Anestis (BMC, 2023)
Abstract Background Firearms account for over 40,000 deaths in the USA each year in addition to thousands of nonfatal injuries. One notable prevention strategy for firearm-related fatalities and nonfatal injuries is safe storage. Safe storage of firearms emphasizes using storage mechanisms that limit ready access of firearms to unauthorized users. Cable locks are one safe storage option that is easy to access and typically free, as they are included in many firearms sales. The present study examined the extent to which firearms retailers notifying purchasers at the point of sale about the included cable locks was associated with subsequent locking device use in two large samples and three subsamples. Exploratory analyses then examined demographic factors associated with frequency of seller notification of locks. Methods Sample 1 included 1203 firearm owners and sample 2 included 1556 firearm owners. Subsamples were drawn from sample 2 to examine if there were differences by state. The three subsamples included firearm owners from Minnesota (n = 515), Mississippi (535), and New Jersey (506). Logistic regressions were used to examine the association between frequency of sellers notifying buyers of locks and subsequent locking device use. Linear regressions were used to examine what demographic factors were associated with greater frequency of seller notification of locking devices. Results Results indicated a general trend such that more frequent notification of cable locks at the point of purchase was associated with greater likelihood of using locking devices to secure firearms. At the subsample level, these findings were most consistent for Mississippi relative to Minnesota and New Jersey. Exploratory analyses generally indicated those who were younger and those living in more densely populated areas were more likely to be notified about cable locks at the point of purchase. Conclusions These findings suggest that interactions about cable locks at the point of firearm purchase has an impact on firearm storage behaviors. Such results indicate that encouraging firearm retailers to have these discussions with those purchasing firearms might be an important strategy for preventing firearm-related fatalities and nonfatal injuries.